Incidence of Type 2 Diabetes in Kuwaiti Children and Adolescents: Results From the Childhood-Onset Diabetes Electronic Registry (CODeR) - Al-Kandari, Hessa; Al-Abdulrazzaq, Dalia; Davidsson, Lena; Sharma, Prem; Al-Tararwa, Abeer; Mandani, Fawziya; Al-Shawaf, Faisal; Al-Hussaini, Fatma; Qabazard, Mariam; Haddad, Dania; Al-Mahdi, Maria; Al-Jasser, Fahad; et al. (Frontiers in Endocrinology, 2019)
Background: Type 2 Diabetes (T2D) in children and adolescents has become an important public health concern due to the increase in childhood obesity worldwide. The urgency to address T2D is evident as children and adolescents are at a higher risk of complications due to prolonged disease duration. We aimed to estimate the incidence rate (IR) of T2D in Kuwaiti children and adolescents aged 14 years and younger between 2011-2013 and to describe their clinical characteristics at the time of diagnosis. Material and Methods: All newly diagnosed patients were registered through the Childhood-Onset Diabetes electronic Registry implemented in Kuwait. Cases who met the 2018 ISPAD guidelines for diagnosis of T2D were included. Results: A total of 32 patients were included, equally distributed gender-wise, with a mean age 12.2 years (±1.7 SD), lower for females than males (11.5 Vs 12.2, p<0.025). Data ascertainment was 94.1% (95%CI; 91.6-96.6%). Overall IR was 2.56 (95% CI; 1.78-3.56) per 100,000 Kuwaiti children and adolescents per year. Most of the patients (n=30; 93.8%) presented with T2D between the ages 10-14 years, with age-specific IR of 8.0 (95%CI; 5.5-11.3). No statistically significant difference between males and females with regards to BMI z scores or HbA1C at diagnosis. Conclusion: The true incidence of T2D in Kuwaiti children and adolescents is expected to be considerably higher as we have reported only symptomatic cases. Future research should focus on screening children and adolescents at risk to enable accurate estimates. More efforts are needed to better understand the clinical course of T2D early in life to improve management, prevent complications and improve quality of life.